Chronic chromosome instability induced by Plk1 results in immune suppression in breast cancer - Kandala, Sridhar; Ramos, Maria; Voith von Voithenberg, Lena; Díaz-Jiménez, Alberto; Chocarro, Sara; Keding, Johanna; Brors, Benedikt; Imbusch, Charles; Sotillo, Rocio (Cell reports, 2023)
Chromosome instability (CIN) contributes to resistance to therapies and tumor evolution. Although natural killer (NK) cells can eliminate cells with complex karyotypes, high-CIN human tumors have an immunosuppressive phenotype. To understand which CIN-associated molecular features alter immune recognition during tumor evolution, we overexpress Polo-like kinase 1 (Plk1) in a Her2+ breast cancer model. These high-CIN tumors activate a senescence-associated secretory phenotype (SASP), upregulate PD-L1 and CD206, and induce non-cell-autonomous nuclear factor κB (NF-κβ) signaling, facilitating immune evasion. Single-cell RNA sequencing from pre-neoplastic mammary glands unveiled the presence of Arg1+ macrophages, NK cells with reduced effector functions, and increased resting regulatory T cell infiltration. We further show that high PLK1-expressing human breast tumors display gene expression patterns associated with SASP, NF-κβ signaling, and immune suppression. These findings underscore the need to understand the immune landscape in CIN tumors to identify more effective therapies, potentially combining immune checkpoint or NF-κβ inhibitors with current treatments.